Illustrate my problem with figure:

enter image description here For a given curve (solid line '-'). $\phi$ is the signed distance function of curve, $n$ is the normal vector at $\phi^{-1} = 0$, the dashed line '--' is the level curve with distance $\eta$.

Define $\kappa$ is the curvature of level curve, I want find the relation between curvature of $\kappa(x)$ and $\kappa(y)$ where $y = x + \eta n$. More detailed, I want express the relation by the form of $ \kappa(y) = a \kappa(x) + O(\eta^2) $ where $a$ is constant or geometry on given curve.

For a simple example. Let curve $\phi^{-1}=0$ is a circle with radius of $r$. Then we have $ \kappa(y) = (1 + \eta \kappa(x) )^{-1} \kappa(x)$ since $\kappa(x) = \frac{1}{r}$, and $\kappa(y) = \kappa(x+\eta n) = \frac{1}{r+\eta}$.

I have try to expansion by Taylor expansion, $\kappa(y) = \kappa(x) + \eta n \cdot \nabla \kappa + O(\eta^2)$. But I want more simple formula since $\nabla \kappa$ is complex to calculate in my problem.

Is there some books or reference recommend for this kind problem? Thanks

  • $\begingroup$ In general, you are talking about parallel curves in the plane if you go a fixed normal distance $\eta$ at each point. It's easier than to work parametrically (say, assuming the original curve is arclength-parametrized). $\endgroup$ – Ted Shifrin Aug 9 '17 at 6:40

This is only intuition, no prove: I'll write $\kappa_\eta(t)$ to denote the curvature of $t\mapsto c(t)+\eta n(t)$ at $t$, where $c$ is the initial curve. By using \begin{equation}|\kappa|=R^{-1}, \end{equation} where $R$ is the radius of the best fitting circle, we get (always for $\eta$ small enough) \begin{equation}\kappa_\eta=-(R+\eta)^{-1}=\frac{-|\kappa|}{1+\eta |\kappa|}=\frac{\kappa}{1-\eta \kappa} \end{equation} for points with initial negative curvature $\kappa$ and \begin{equation}\kappa_\eta=(R-\eta)^{-1}=\frac{|\kappa|}{1-\eta |\kappa|}=\frac{\kappa}{1-\eta \kappa} \end{equation} for points with initial positive curvature $\kappa.$ So in general (for $\eta$ small enough) \begin{equation}\kappa_\eta=\frac{\kappa}{1-\eta \kappa}=\kappa\sum_{i=0}^\infty (\kappa \eta)^i=\kappa+\kappa^2\eta+\kappa^3\eta^2+... \end{equation}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.